The Use of Deixis in Taylor Swift’s Cowboy Like Me - Dayana, Sri; Syatroh, Isry Laila; Naksabandi, Arip (PROJECT (Professional Journal of English Education), 2025)
Deixis is a pragmatic study that examines an expression that refers to the speaker's condition and can only be explained by the speaker himself. In this study, researchers examined the types of deixis and their meanings in the lyrics of singer Taylor Swift's song "Cowboy Like Me." The theory used in this research is Levinson's theory. This study uses a descriptive qualitative approach, with data in the form of words, phrases, clauses, or sentences contained in the lyrics of the song "Cowboy Like Me." In this study, the researchers found the types of deixis found in personal deixis, place deixis, time deixis, discourse deixis, and social deixis, which contained 82 data. The researcher found 53 person deixis, two time deixis, three-place deixis, five social deixes, and 19 discourse deixis.